Assessment of the quality of public transport services in the city of Piotrków Trybunalski - Kowalska, Aleksandra (Developing Sustainable, Smart and Resilient Urban Transportation Systems - Residents’ Perspective, 2024)
Transport has been an inseparable element of human existence since the beginnings of civilization. Currently, we can increasingly observe the direct impact of urban transportation on various aspects of human life. The better it functions, the higher the quality of life for the residents of a given city. Local authorities should ensure the continuous development of public transportation infrastructure and improve the quality of services provided to encourage the population to use public transportation more frequently. The main objective of this chapter is to present transportation solutions in the public transportation system using the example of the city of Piotrków Trybunalski, as well as to assess the level of passenger satisfaction with public transportation services in the city of Piotrków Trybunalski. The chapter presents the transportation solutions implemented in the city of Piotrków Trybunalski and provides the results of a study on the perception of service quality provided by the Municipal Communication Company Ltd. in Piotrków Trybunalski.